Pengaruh perbedaan jenis pelarut dalam proses ekstraksi buah mengkudu (Morinda citrifolia L.) pada pakan terhadap viabilitas protozoa dan produksi gas in-vitro - Deni Ramdani; marjuki majuki; Siti Chuzaemi (Faculty of Animal Science, Universitas Brawijaya, 2017)
The aim of this study to determine the best solvent for noni fruits (Morinda citrifolia L.) extraction processes that can reduce the growth of ruminal protozoa and gas production. This reaserch used a nested on randomized block design with 2 factors of treatment and 3 groups as replicates, if there was significant different would be tested by Duncan’s Multiple Range Test Methode. EM was noni fruits extract which methanol used as solvent, and EA was noni fruits extract which aquadest used as solvent. The result show that the number of protozoa and gas production were decreased on additional of noni fruits extract with methanol solvent (P<0,05). The conclusion of this research is the used of methanol is the best solvent in noni fruits extraction processes to reduce a number of ruminal protozoa and increase of degradability.